Decreased Transport Restores Growth of a Salmonella enterica apbC Mutant on Tricarballylate - Boyd, Jeffrey M. (American Society for Microbiology, 2012)
Mutants of Salmonella enterica lacking apbC have nutritional and biochemical properties indicative of defects in iron-sulfur ([Fe-S]) cluster metabolism. An apbC mutant is unable to grow on tricarballylate as a carbon source. Based on the ability of ApbC to transfer an [Fe-S] cluster to an apoprotein, this defect was attributed to poor loading of the [Fe-S] cluster-containing TcuB enzyme. Consistent with these observations, a previous study showed that overexpression of iscU, which encodes an [Fe-S] cluster molecular scaffold, suppressed the tricarballylate growth defect of an apbC mutant (J. M. Boyd, J. A. Lewis, J. C. Escalante-Semerena, and D. M. Downs, J. Bacteriol. 190:4596–4602, 2008). In this study, tcuC mutations that suppress the growth defect of an apbC mutant by decreasing the intracellular concentration of tricarballylate are described. Collectively, the suppressor analyses support a model in which reduced TcuB activity prevents growth on tricarballylate by (i) decreasing catabolism and (ii) allowing levels of tricarballylate that are toxic to the cell to accumulate. The apbC tcuC mutant strains described here reveal that the balance of the metabolic network can be altered by the accumulation of deleterious metabolites.